Stability of nutrients in complex liquid and powder food matrices: learnings from shelf-life studies in foods for special medical purposes - Laurent Ameye; Sophie de Brouwer; Donald L. Gilliland; Julia Heckmann; Kaushik Janakiraman; Bridget-Anne Kirwan; Xavier Lavigne; Francisco Moya; Vanessa Zammit (Current Research in Food Science)
We investigated the effects of physical state, temperature, pH, protective atmosphere, protein hydrolysis, fats, fibre, packaging and flavour on nutrient degradation by analyzing the results of shelf-life studies of 1400 recipes of Foods for Special Medical Purposes (FSMP). For each nutrient, the adaptive LASSO method was applied to identify which factors drive degradation. Degradation percentage was estimated by repeated measure model using the list of identified factors and time as covariates. Nutrients that had little or no degradation under all tested conditions included fat, protein, individual fatty acids, minerals and the vitamins B2, B6, E, K, niacin, biotin and beta carotene. Important nutrient degradation which was, mainly driven by temperature, were only observed in vitamin A (powder products), vitamin C, B1 and D (liquid products) and pantothenic acid (acidified liquids). These nutrients used as tracers in stability studies would be sufficient to confirm the nutritional suitability of products until their end of shelf-life. Our results show that the most important factors driving nutrient degradation were liquid format, temperature and pH. The fat content, relative humidity, presence of fibre, flavours or packaging size/type did not impact on the stability of any nutrients. These results provide a sound basis to guide health authorities to define which nutrients should ideally be included in FSMP shelf-life studies in addition to providing valuable insight into which factors impact on nutrient degradation in general.